2020
DOI: 10.1111/1755-0998.13130
|View full text |Cite
|
Sign up to set email alerts
|

The case of an arctic wild ass highlights the utility of ancient DNA for validating problematic identifications in museum collections

Abstract: Museum collections are essential for reconstructing and understanding past biodiversity. Many museum specimens are, however, challenging to identify. Museum samples may be incomplete, have an unusual morphology, or represent juvenile individuals, all of which complicate accurate identification. In some cases, inaccurate identification can lead to false biogeographic reconstructions with cascading impacts on paleontological and paleoecological research. Here, we analyzed an unusual Equid mandible found in the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 17, 2021. ; https://doi.org/10.1101/2021.12.16.472923 doi: bioRxiv preprint iterative mapping tools are available; mapping interactive assembler (MIA) was originally designed to assemble a number of Neandertal and early modern human mitochondria (Green et al, 2008), but has been used for non-human species (Vershinina et al, 2020). Despite its utility, when using a more distant bait reference, MIA requires much more memory and CPU time than MITObim (Hahn et al, 2013), and is therefore not as suitable for species when only relatively divergent bait references are available, such as the datasets tested here.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 17, 2021. ; https://doi.org/10.1101/2021.12.16.472923 doi: bioRxiv preprint iterative mapping tools are available; mapping interactive assembler (MIA) was originally designed to assemble a number of Neandertal and early modern human mitochondria (Green et al, 2008), but has been used for non-human species (Vershinina et al, 2020). Despite its utility, when using a more distant bait reference, MIA requires much more memory and CPU time than MITObim (Hahn et al, 2013), and is therefore not as suitable for species when only relatively divergent bait references are available, such as the datasets tested here.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, molecular identification using aDNA can provide an unequivocal identification (Miller, 2007). Vershinina and collaborators provide an example of how aDNA from NHC specimens can help us correctly identify samples and avoid false biogeographic reconstructions (Vershinina, Kapp, Baryshnikov, & Shapiro, 2019). Using ancient DNA, they corrected a morphological misidentification made from a partial jaw of an Equid, initially described as Equus hemionus, the Asiatic wild ass (Cucchi et al., 2017; Vershinina et al., 2019).…”
Section: Summary Of the Special Featurementioning
confidence: 99%
“…Vershinina and collaborators provide an example of how aDNA from NHC specimens can help us correctly identify samples and avoid false biogeographic reconstructions (Vershinina, Kapp, Baryshnikov, & Shapiro, 2019). Using ancient DNA, they corrected a morphological misidentification made from a partial jaw of an Equid, initially described as Equus hemionus, the Asiatic wild ass (Cucchi et al., 2017; Vershinina et al., 2019). Molecular results showed that the partial jaw belonged to E. caballus, motivating a substantial reinterpretation of the evolutionary history of Equids, which in addition to wild asses includes horses, zebras, kiangs and donkeys (Cucchi et al., 2017; Vershinina et al., 2019).…”
Section: Summary Of the Special Featurementioning
confidence: 99%
See 1 more Smart Citation
“…However, these protocols are primarily optimized to deal with poor DNA quality due to contamination and fragmentation (Rohland, Harney, Mallick, Nordenfelt, & Reich, 2015), designed to enrich endogenous DNA over contaminations (Horn, 2012) and therefore target only specific parts of the genome (Knyshov, Gordon, & Weirauch, 2019;Suchan et al, 2016). Many of the protocols also still require higher amounts of input DNA or tissue than used in this study (Gamba et al, 2016;Shapiro et al, 2019;Tsai et al, 2019;Vershinina, Kapp, Baryshnikov, & Shapiro, 2020). Therefore, these methods are more targeted to fragmented DNA and less cost-and time-efficient compared to the presented workflow.…”
Section: Whole Genome Sequencingmentioning
confidence: 99%